Phenology and yield of peach cultivars - Almeida, Gustavo Klamer de; Magrin, Fernanda Pelizzari; Soldatelli, Pâmella; Fioravanço, João Caetano (Revista de Ciências Agroveterinárias, 2015)
The goal of the current work was to evaluate the phenology and yield of peach cultivars exhibiting intermediate to high winter chilling requirements. The experiment was established in Vacaria, RS, during the growing seasons of 2009/10 and 2012/2013. Eight scion cultivars (Barbosa, Chimarrita, Chiripá, Della Nona, Eragil, Maciel, Rubidoux and Seleção Cambará) grafted on peach seedling rootstocks were evaluated, in orchards of 4.7 m spacing between lines and 2.5 m between plants. The plots were designed as random blocks, with eight treatments (cultivars) and three replicates. Maciel and Chimarrita cultivars exhibited precocious flowering and fruit ripening, generally in July and December, respectively; Rubidoux displayed late flowering and ripening, in September and February, respectively. The Barbosa, Rubidoux and Maciel cultivars produced fruits with more than 130 g, on average, while those from Seleção Cambará weighted less than 100 g. All evaluated cultivars were well adapted to the climate conditions of Vacaria, RS, as demonstrated by yields higher than 20 t ha-1 in the fourth year of production. The Barbosa, Della Nona and Eragil cultivars are the most recommended to crop in Vacaria, RS, considering the fl owering date, yield, fruit quality and development of plants.